Critical Thinking Characteristics of Female National Science Olympiad Participants in Solving Mathematics Problems - Dian Septi Nur Afifah Afifah; Muhammad Ilman Nafi'an; Arum Purba Sulistyani (Athena: Journal of Social, Culture and Society, 2023)
This study aims to describe the characteristics of critical thinking of female OSN participants in solving math problems. This research is a case study qualitative approach. The research subjects were female participants of OSN SMP Mathematics Tulungagung Regency. The subject selection technique was snowball sampling. Research instruments were test questions and interview guidelines. Data collection techniques include written tests, interviews, documentation. Data validity checking triangulation techniques and reference adequacy. Data analysis includes data reduction, data presentation, conclusion drawing. Based on the research results, the subject fulfills 11 indicators, namely (1) reading carefully, repeatedly, writing mathematical sentences without explaining, focusing the question, (2) explaining the plan by understanding the problem, choosing the formula, writing the formula, (3) working coherently, structured, according to the formula, (4) explaining the information obtained by remembering the material and formulas used, (5) explained the steps to solve the problem clearly, coherently, thorough workmanship, and confidently, (6) argued according to his knowledge, relevant, and accurate but not logical, (7) used one solution and detected other possible plans by trying first, (8) explained other possible steps by paying attention to each stage, (9) tried to solve based on the plan made, (10) found the value of the element subsumed in the formula, the answer was correct and (11) was sure the answer was correct, checking by checking the calculation of the substitution of numbers in the formula from the beginning